Innovative Approach to Adjustable Color Temperature in LED Luminaires - Tascı, Burak; Erol, Yavuz (My University, 2025)
The field of lighting technology is rapidly evolving. Among these technologies, Light Emitting Diode (LED) systems stand out as highly efficient light sources. LEDs are manufactured with various characteristics and structures. For instance, RGB (Red Green Blue) LEDs are capable of producing a wide spectrum of colors. By using RGB LEDs, it is also possible to achieve white light with different color temperatures Color temperature plays a crucial role in how our eyes perceive the colors of objects. We can observe the true colors of an object under daylight illumination with a color temperature of 6500K. The same object may appear differently under lighting with various color temperatures. Consequently, there has arisen a need to adjust different color temperatures within a single lighting fixture. Existing LED lighting systems often struggle with achieving precise control over color temperature and brightness due to limitations in hardware integration and computational efficiency. Additionally, these systems may require costly sensors or lack the flexibility to adapt to varying environmental conditions. To address these gaps, the proposed system integrates PSoC technology with an AS7261 XYZ Chromatic White Color Sensor, enabling real-time adjustments of color temperature and brightness with enhanced precision and cost-effectiveness. In this study, a design of an adjustable LED luminaire in terms of both brightness and color temperature has been developed using PSoC (Programmable System on Chip) technology, which is gaining significant traction and importance in the field of embedded systems. The necessary XYZ data for the color temperature of the luminaire, which consists of RGB LEDs, were obtained from the AS7261 XYZ Chromatic White Color Sensor. The XYZ information gathered from this sensor was utilized in the algorithm of the designed system. By adjusting the brightness levels at which the RGB LEDs operate according to the desired color temperature and illumination level, the system was successfully implemented. This innovative approach has practical applications in energy-efficient lighting systems, industrial production processes, and customizable illumination solutions for residential, commercial, and automotive environments, highlighting its potential for widespread industrial adoption.
Keywords: CCT tunable LED luminaire; CCT control; Embedded PSoC system